A New Innovation Platform Development To Expand New Market Of Services (Case Study : Makaffah Salon And Bridal) - Sukmawati Bachtiar; Wawan Dhewanto (UNIVED Press, 2025)
Innovation and digital transformation have become essential for businesses to remain competitive in the evolving market landscape. Makaffah Salon and Bridal, established in 2015 in Cimahi, West Java, has successfully navigated challenges, including the COVID-19 pandemic, under CV Young Enterprise Indonesia. However, to sustain growth and expand its market reach, the salon must embrace digitalization to enhance service efficiency, customer experience, and business operations. This research aims to explore the impact of digital transformation, personalization, and home-based service innovations on operational efficiency, customer satisfaction, and market expansion. This study adopts a mixed-method approach, integrating qualitative and quantitative methodologies. The research follows the Design Thinking framework, where the first phase, Empathize, is tested through in-depth interviews with key stakeholders, including salon managers, employees, and customers, to identify critical pain points and innovation opportunities. The insights from the qualitative phase inform the development of a digital innovation model based on Lean Startup Methodology Activities, Disruptive Innovation Theory, and the Digital Transformation Framework. In the final phase, the proposed solutions are quantitatively tested through a structured survey, allowing for statistical validation of the impact of digital innovations on operational efficiency, customer satisfaction, and business scalability. The findings are expected to reveal that adopting digital solutions significantly improves operational efficiency, enhances customer satisfaction through personalized services, and increases accessibility via home-based service models. This research contributes to the growing body of literature on digital transformation in the beauty industry and provides practical recommendations for Makaffah Salon and Bridal to implement a data-driven innovation platform that meets evolving consumer demands.